2015
DOI: 10.1145/2738037
|View full text |Cite
|
Sign up to set email alerts
|

A Baseline Model for Software Effort Estimation

Abstract: Software effort estimation (SEE) is a core activity in all software processes and development lifecycles. A range of increasingly complex methods has been considered in the past 30 years for the prediction of effort, often with mixed and contradictory results. The comparative assessment of effort prediction methods has therefore become a common approach when considering how best to predict effort over a range of project types. Unfortunately, these assessments use a variety of sampling methods and error measure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(114 citation statements)
references
References 47 publications
1
113
0
Order By: Relevance
“…More recently, Whigham et al found that claims made in two recent cost estimation studies could not be confirmed by independent analyses [47]. RR emphasizes the need to specify, fully, any statistical analysis, in order to address problems such as these.…”
Section: Problems With Empirical Software Engineering Practicementioning
confidence: 99%
“…More recently, Whigham et al found that claims made in two recent cost estimation studies could not be confirmed by independent analyses [47]. RR emphasizes the need to specify, fully, any statistical analysis, in order to address problems such as these.…”
Section: Problems With Empirical Software Engineering Practicementioning
confidence: 99%
“…Miyazaki et al [36] employed robust regression (RoR) to predict effort of new project, which is an alternative to OLS regression with the advantage of being less vulnerable to the existence of outliers in the data. Recently, Whigham et al [9] addressed an automatically transformed linear model (ATLM) and recommended it as a baseline model for comparison against SEE methods.…”
Section: Effort Estimation Methodsmentioning
confidence: 99%
“…In recent years, several estimation methods have been presented [1][2][3][4][5][6][7][8][9][10]. Some well-known machine learning methods have also been employed for estimation, such as classification and regression tree (CART) [11] and neural networks (NN) [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…The estimation model considered in this study is the Automatically Transformed Linear Model (ATLM) proposed by Whigham et al [3]. ATLM was developed using multiple linear regression with a minimal threshold to act as a baseline for software effort estimation.…”
Section: B Experimental Setup and Evaluation Measuresmentioning
confidence: 99%
“…We employed the Mean Absolute Error (MAE) which has been proven reliable by Foss et al [9] and considered in previous studies [3][10] [2]. MAE is a risk function that measures the average absolute deviation of the estimated effort values from the true effort values.…”
Section: B Experimental Setup and Evaluation Measuresmentioning
confidence: 99%